(untitled) (Indian Journal of Public Health Research & Development, 2023)
Background: Appendicitis is quite common surgical emergency in children because it is longer in children ranges from 2-20 cm than adult 6-10 cm. Moreover it is most constricted part of GIT like pharynx. Method: 80 children (40 male and 40 females) below 10 years having symptoms of appendicitis and confirmed byUSG/ST scan were operated by General anaesthesia and dissected part was sent to histo-pathology test to rule out the exact pathology. Results: Highest incidence of acute appendicitis was observed in both sexes 23 (57.5%) male, 20 (50%)female and least number of perforated appendicitis 10 (25%) in male, 4 (10%) in female was observed. Conclusion: Present pragmatic study of appendicitis having acute, chronic and perforation will help the surgeon to treat efficiently to avoid morbidity and mortality in children.